Dendrocaustology – the science of wildland fires - Lourenço, Luciano (2014)
Wildland fires are a generalised and recurrent problem. However, due to the high number of natural and human variables directly and indirectly involved, the study of Wild land fires is extremely complex and difficult. Step by step, with the universalization of scientific research on wild land fires we have witnessed the gradual establishment of a new, very particular science, given that the same object of study is being approached by many sciences, methodologies, scales of analysis, and even with different aims… Nevertheless, there is no specific designation for this science. We propose to designate the science of wild land fires as Dendrocaustology so that fire scientists can, from now on, have a single word which they can use to designate their science.